Evaluating different concentrations of hydrogen peroxide in an automated room disinfection system. (1st September 2016) - Murdoch, L.E.; Bailey, L.; Banham, E.; Watson, F.; Adams, N.M.T.; Chewins, J.
Abstract: A comparative study was made on the efficacy of 5, 10 and 35% weight by weight (w/w) hydrogen peroxide solutions when applied using an automated room disinfection system. Six‐log biological indicators of methicillin‐resistant Staphylococcus aureus (MRSA) and Geobacillus stearothermophilus were produced on stainless steel coupons and placed within a large, sealed, environmentally controlled enclosure. Five percent hydrogen peroxide was distributed throughout the enclosure using a Bioquell hydrogen peroxide vapour generator (BQ‐50) for 40 min and left to reside for a further 200 min. Biological indicators were removed at 10‐min intervals throughout the first 120 min of the process. The experiment was repeated for 10 and 35% hydrogen peroxide solutions. Five percent and 10% hydrogen peroxide solutions failed to achieve any reduction of MRSA, but achieved full kill of G. stearothermophilus spores at 70 and 40 min respectively. Thirty‐five percent hydrogen peroxide achieved a 6‐log reduction of MRSA after 30 min and full kill of G. stearothermophilus at 20 min. The concentration of 5% hydrogen peroxide within the enclosure after the 200‐min dwell was measured at 9·0 ppm. This level exceeds the 15‐min Short Term Exposure Limit (STEL) for hydrogen peroxide of 2·0 ppm. Users of automated hydrogen peroxide disinfection systems should review system efficacy and room re‐entry protocols in light of these results. Significance and Impact of the Study: This research allows hospital infection control teams to consider the impact and risks of using low concentrations of hydrogen peroxide for disinfection within their facilities, and to question automated room disinfection system providers on the efficacy claims they make. The evidence that low concentration hydrogen peroxide solutions do not rapidly, autonomously break down, is in contradiction to the claims made by some hydrogen peroxide equipment providers and raises serious health and safety concerns. Facilities using hydrogen peroxide systems that claim autonomous break down of hydrogen peroxide should introduce monitoring procedures to ensure rooms are safe for re‐entry and patient occupation.